2002
DOI: 10.1152/jappl.2002.92.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure and mesenteric resistance arterial function after spaceflight

Abstract: Ground studies indicate that spaceflight may diminish vascular contraction. To examine that possibility, vascular function was measured in spontaneously hypertensive rats immediately after an 18-day shuttle flight. Isolated mesenteric resistance arterial responses to cumulative additions of norepinephrine, acetylcholine, and sodium nitroprusside were measured using wire myography within 17 h of landing. After flight, maximal contraction to norepinephrine was attenuated (P < 0.001) as was relaxation to acetylch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
15
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 35 publications
4
15
0
Order By: Relevance
“…The primary unanswered question regarding vascular alterations associated with spaceflight is the stimulus for the change. Results from the present and previous studies (30, 31) show impaired contraction of smooth muscle cells of arteries and veins from SF rats and mice. In addition, pregnant rats flown on the Cosmos 1514 mission had prolonged labor (62), and rats flown on Cosmos 1667 had distended stomachs filled with food (63), indicating the possible impairment of uterine and stomach smooth muscle contraction with spaceflight.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…The primary unanswered question regarding vascular alterations associated with spaceflight is the stimulus for the change. Results from the present and previous studies (30, 31) show impaired contraction of smooth muscle cells of arteries and veins from SF rats and mice. In addition, pregnant rats flown on the Cosmos 1514 mission had prolonged labor (62), and rats flown on Cosmos 1667 had distended stomachs filled with food (63), indicating the possible impairment of uterine and stomach smooth muscle contraction with spaceflight.…”
Section: Discussionsupporting
confidence: 68%
“…1 A, B , respectively). In one of only two studies to previously examine the effects of spaceflight on intrinsic vasomotor responsiveness, Hatton et al (30) reported that microgravity blunted NE‐mediated vasoconstriction of mesenteric arteries from SF rats. However, because these animals were spontaneously hypertensive, the effects of spaceflight on vascular responses in normotensive animals was uncertain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Direct measures of blood flow (31) and the lack of change in vascular structure (22,28,56) indicate that neither blood flow nor arterial pressure are significantly altered when rats are in an unloaded position. It has recently been suggested that decrements in peripheral artery vasoconstrictor responsiveness may be associated with a circulating systemic factor(s) that is altered during unloading (5).…”
Section: Fig 5 Representative Profiles Of the Vasoconstrictor Dynammentioning
confidence: 99%
“…Previous work demonstrated that actual and simulated microgravity can adversely affect smooth muscle contractile function in arteries (12,25,45), arterioles (11), veins (16), and the uterus (7). We hypothesized that microgravity could also alter lymphatic muscle contractility.…”
mentioning
confidence: 99%